Effect of Two Heavy Metals (Zn and Ni) on Growth of In vitro Hairy Root Cultures of Indian Mustard Brassica juncea L. - Ismail, A. Mohamed; Theodor, P. Agastian (Research Perspectives of Microbiology and Biotechnology Vol. 1, 2024)
Metals are natural components in soil with a number of heavy metals being required by plants as micronutrients. Since the beginning of the Industrial Revolution, there has been a dramatic increase in toxic metal pollution of the biosphere. Roots are the plant parts, which facilitate the primary contact between a plant and a pollutant. Culture of genetically transformed hairy roots of hyperaccumulator plant sp. Brassica juncea L. grown in vitro was established to study the potential of in vitro hairy root cultures for the uptake and accumulation of heavy metals (Ni and Zn) for their growth and biomass from an aquatic environment. All the chemicals and reagents in this experiment were of Analytical grade and were obtained from Hi Media Laboratories Pvt ltd., Mumbai, India. At elevated concentrations of Ni and Zn metals, hairy roots showed exponential growth and accumulation. In lower concentrations, Zn might have no effect on the growth of root biomass and also found to be it cause no dramatic decrease in root growth even if they are accumulated. At higher concentrations of Zn, B. Juncea hairy roots were not only found to be tolerant to Zn and also had the capacity to increase their root biomass and no growth retardation was seen. All concentrations of Ni showed a drastic change in root biomass growth irrespective of the duration of incubation periods. Ni in higher concentrations caused an exponential increase in root biomass growth and Ni showed no toxicity symptoms in hairy roots even at higher concentrations for a longer time up to 8 weeks of our study period. Ni was found to be an essential micronutrient for the growth of hairy root biomass. From this study, it was cleared and concluded that hairy roots of in vitro grown hyperaccumulator plant culture system could be a useful and effective model (as it needs metals for their root biomass growth) to study the metal uptake and accumulation from an aquatic environment.